Biochemical Characteristics of Three Laccase Isoforms from the Basidiomycete Pleurotus nebrodensis - Yuan, Xianghe (Molecules, 2015)
The characterization of three laccase isoforms from Pleurotus nebrodensis is described. Isoenzymes Lac1, Lac2 and Lac3 were purified to homogeneity using ion exchange chromatography on DEAE-cellulose, CM-cellulose and Q-Sepharose and a gel filtration step on Superdex 75. The molecular weights of the purified laccases were estimated to be 68, 64 and 51 kDa, respectively. The isoenzymes demonstrated the same optimum pH at 3.0 but slightly different temperature optima: 50–60 °C for Lac1 and Lac3 and 60 °C for Lac2. Lac2 was always more stable than the other two isoforms and exposure to 50 °C for 120 min caused 30% loss in activity. Lac2 was relatively less stable than the other two isoforms when exposed to the pH range of 3.0–8.0 for 24 h, but inactivation only occurred initially, with around 70% residual activity being maintained during the whole process. Oxidative ability towards aromatic compounds varied substantially among the isoforms and each of them displayed preference toward some substrates. Kinetic constants (K(m), K(cat)) were determined by using a 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) assay, with Lac3 showing the best affinity and Lac2 displaying the highest catalytic efficiency. Amino acid sequences from peptides derived from digestion of isoenzymes showed great consistency with laccases in the databases.